A novel correlative model of failure mechanisms for evaluating MEMS devices reliability. (September 2016) - Li, Yaqiu; Sun, Yufeng; Hu, Weiwei; Wang, Zili
Abstract: The failure behavior of MEMS can be regarded as the result of certain dependent failure mechanisms in accordance with device's internal attributes and external environment. However, the correlative effects among multiple mechanisms governing the failure process of MEMS have not been well characterized. This paper reviews significant failure mechanisms of MEMS products and proposes a new correlative model for MEMS reliability evaluation. Based on the nature of different failure mechanisms, dependent factors of these correlations are discussed and mathematical models are derived. With a case, reliability of a sort of RF switch is evaluated taking into account the failure mechanism correlative effects, and sensitivity analysis is conducted to assess the effects of the model parameters on reliability function R ( t ) and failure probability density function f ( t ). Highlights: A new correlative model for MEMS reliability evaluation is proposed; Mathematical models about the correlative effects of degradation and catastrophic failure mechanisms are derived; The importance of model parameters related the design and performance characters of MEMS are analyzed.